Kecanduan Bermain Game Online terhadap Kepribadian Sosial pada Anak - A. Yuna Triana; Sudarman, Sudarman; Nur Ilah Padhila (Window of Nursing Journal, 2023)
Addicted to online games if you play them too much, there will be a negative impact from playing online games, namely learning motivation, decreased, decreased learning achievement. This study aims to determine the description of addiction to playing online games on social personality in children at SDN 247 Sorowako. The research design used is quantitative research with a Cross Sectional Study approach. This research was conducted at SDN 247 Sorowako in April 2022. The sample was determined using a simple random sampling technique with a sample size of 149 students. The relationship test was carried out using the Chi Square statistical test with a significance level of <0.05. The results showed that the majority of online game addictions were at a high level of addiction as many as 119 people (79.9% and the majority had good personalities as many as 107 people (71.8%). The conclusion from the results of this study showed that the results obtained from the description of addiction to playing online games for students at SDN 247 Sorowako is a high majority, while the results from the social personality description are a good majority. It is hoped that the teachers at SDN 247 Sorowako will educate students about the negative effects of online games.